If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(m + -30) = -6m Reorder the terms: 2 + -1(-30 + m) = -6m 2 + (-30 * -1 + m * -1) = -6m 2 + (30 + -1m) = -6m Combine like terms: 2 + 30 = 32 32 + -1m = -6m Solving 32 + -1m = -6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6m' to each side of the equation. 32 + -1m + 6m = -6m + 6m Combine like terms: -1m + 6m = 5m 32 + 5m = -6m + 6m Combine like terms: -6m + 6m = 0 32 + 5m = 0 Add '-32' to each side of the equation. 32 + -32 + 5m = 0 + -32 Combine like terms: 32 + -32 = 0 0 + 5m = 0 + -32 5m = 0 + -32 Combine like terms: 0 + -32 = -32 5m = -32 Divide each side by '5'. m = -6.4 Simplifying m = -6.4
| 6y-2[7(1y+1)+4]=10y | | 8x+15=-4x+63 | | 12a-6+8=2 | | -3x^2+13-4= | | 15x-10=9x+26 | | 4d+d=40 | | x^2+11x+2= | | 6+-1(8-4m)=2(2m-1) | | 3x+9=6x+4 | | x^2-36x=8140 | | 8(x-.75)+12=-10 | | 1-4n=29 | | F(x)=13x+7 | | -1x-3=-2x-4 | | 5-(8+10)=8+5 | | 10+4q=34 | | 18+-1(3-2y)=3(y-5) | | x^2-36x=5605 | | u^2-4u+4-80=0 | | 8c+8=224 | | r+at=v | | 10-9x-5=-(3x+5)-2(2x-5) | | e-(-73)=-22 | | t(-16)=9 | | -5a-7+4a=-(9-7) | | 102=-7r-3 | | t(-16)=-9 | | b=-4t^2 | | v^2+20v=0 | | .3(12x-15)=3x+9 | | y^2-8y+16=2y^2-12y-5 | | 0.4x-12=-22 |